2014
DOI: 10.7241/ourd.20143.64
|View full text |Cite
|
Sign up to set email alerts
|

The comparison study of 5 Fluorouracil vs. cryotherpy in the treatment of the backhand resistant common wart

Abstract: Introduction: Wart is a common disease which is caused by a group of viruses called Human Papilloma Virus. The most prevalent type of wart is common wart and the most prevalent site of involvement is hands. Complete recovery, no recurrency and effectiveness in all patients are not obtained by any of therapeutic methods, so in this study we decided to compare therapeutic effects of 5 Fluorouracil (FU) with cryotherapy in treatment of common warts of backhand. Material and Methods: In this study, in a one year p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…This is also supported by Asghariazar R et al who reported that 60% positive response was achieved in the 5-FU group in comparison to 26.7% positive response in the cryotherapy group, p <0.05. Asghariazar et al demonstrated that having scars was the only effect in the 5-FU group that was equal with the cryotherapy group19 .…”
mentioning
confidence: 94%
“…This is also supported by Asghariazar R et al who reported that 60% positive response was achieved in the 5-FU group in comparison to 26.7% positive response in the cryotherapy group, p <0.05. Asghariazar et al demonstrated that having scars was the only effect in the 5-FU group that was equal with the cryotherapy group19 .…”
mentioning
confidence: 94%